(untitled) (Research Announcements "Heritage BG", 2025)
The text announces the beginning of a process of digitizing a 16 mm video tapes collection in the Folk Music Archive of the Institute of Art Studies which has remained inaccessible for over three decades and whose digitization is now possible thanks to the ‘Cultural Heritage in the Archives of the Institute of Art Studies: An Interactive Map of the Arts in Bulgaria’ project. Brief historical data on the collection have been introduced, the first documents of which date from 1954. Based on the first digitized and reviewed tapes, some characteristics of the stored materials have been presented as well as the stages and problems in their restoration and subsequent digital processing. The importance of the collection content for future work in various scientific areas, and more specifically ethnomusicology and ethnochoreology in Bulgaria, has been commented on. References: Botuscharov 1973: Botuscharov, Lyuben. Vaprosi na katalogizatsiyata na balgarskiya muzikalen folklore v arhiva na Instituta za muzikoznanie pri BAS. Sofia, manuscript. Dimov 2016: Dimov, Ventsislav. Raina Katsarova i nay-rannite terenni zvukozapisi na traditsionna muzika ot Balgariya. – Bulgarian Musicology, No 1, 33-67. Djidjev 2009: Djidjev, Todor. Problemi na dokumentiraneto i notiraneto na narodnata muzika dnes. In: Folklor i savremennost. Sbornik statii. Sofia, 24-29. Kumichin 2017: Kumichin, Maria. Nauchnata deynost na Todor Todorov v konteksta na balgarskata muzikalna folkloristika ot vtorata polovina na XX vek. PhD Dissertation, IAS, Music Department, Sofia. Naydenova 2015: Naydenova, Goritsa. Muzikalnofolklornite dialekti na Elena Stoin v zvuk. Sofia. Naydenova 2021а: Naydenova, Goritsa. Ivan Kachulev, muzikalnite instrumenti i zvukovata sreda. Terenni materiali i nauchno delo. Sofia. Naydenova 2021b: Naydenova, Goritsa. Nauchnite arhivi na Instituta za izsledvane na izkustvata: spetsifiki i nyakoi problemi pri vavezhdaneto im v bazi danni. – Bulgarian Musicology, Special Issue, 7-40. Statulov 2021: Statulov, Deyan. Personalnite fondove v arhiv ‘Ekranni izkustva’ v konteksta na obshtestvenite filmovi arhivi v Balgariya: problemi i vazmozhnosti za opazvaneto im. – Bulgarian Musicology, Special Issue, 150-160. Stoin 1981: Stoin, Elena. Muzikalno-folklorni dialekti v Balgariya. Sofia. Todorov 2002: Todorov, Todor. Vasil Stoin. Zhivot i delo. Sofia. Fügedi 2011: Fügedi, János. The Difference Between the Factual and Dancer’s Inner Reresentation of Movement Rhythm. – In: Proceedings of the 27th Conference. Budapest, 59-69. Fügedi 2015: Fügedi, János. Unheard but Visible – Defining Dance and Music Synchrony in Silent Films. – Acta Ethnographica Hungarica, No 60 (1), 171-183. Nettl 1964: Nettl, Bruno. Theory and Method of Ethnomusicology. New York. Archives: SA – BAS 1955: Scientific Archives, BAS, f. 83, op. 1, a.e. 41. SA – BAS 1957: Scientific Archives, BAS, f. 83, op. 1, a.e. 58